VERTICAL DATUM UNIFICATION IN ACCORDANCE WITH JAVA-SUMATERA UNDER SEA GAS TRANSMISSION PIPE SETTING PROJECT - Leonardo Firmansyah (NIM 25105004), Risteruw
ABSTRACT: Java-Sumatera under sea gas transmission pipe setting is a project which spread through land and sea. Considering dynamic nature of the sea and distance between Java and Sumatera, thus tidal characteristics between those islands will distinguish. The difference of tidal characteristics will result difference of vertical datum level, hence each island will have its own vertical datum. Inconsistencies of vertical datum will finally causing seabed deep discontinuity. To overcome this situation it is required vertical datum unification, so that vertical datum will remain on the same reference system. In general, ideal vertical datum characteristic is based on equipotential surface. Vertical datum acquired from tidal survey of each island is categorized as Mean Sea Level (MSL) of its own island and not take place on the same equipotential surface. As a result those MSL must be transformed in to a same equipotential surface. Within this condition, geoid was chosen as equipotential surface. In practice, geoid is considered as an equipotential surface which closes to errorfree MSL.